Matrix ageing and vascular impacts: focus on elastin fragmentation. Issue 3 (22nd March 2016) - Duca, Laurent; Blaise, Sébastien; Romier, Béatrice; Laffargue, Muriel; Gayral, Stéphanie; El Btaouri, Hassan; Kawecki, Charlotte; Guillot, Alexandre; Martiny, Laurent; Debelle, Laurent; Maurice, Pascal
Abstract: Cardiovascular diseases (CVDs) are the leading cause of death worldwide and represent a major problem of public health. Over the years, life expectancy has considerably increased throughout the world, and the prevalence of CVD is inevitably rising with the growing ageing of the population. The normal process of ageing is associated with progressive deterioration in structure and function of the vasculature, commonly called vascular ageing. At the vascular level, extracellular matrix (ECM) ageing leads to molecular alterations in long half-life proteins, such as elastin and collagen, and have critical effects on vascular diseases. This review highlights ECM alterations occurring during vascular ageing with a specific focus on elastin fragmentation and also the contribution of elastin-derived peptides (EDP) in age-related vascular complications. Moreover, current and new pharmacological strategies aiming at minimizing elastin degradation, EDP generation, and associated biological effects are discussed. These strategies may be of major relevance for preventing and/or delaying vascular ageing and its complications.